| r (t)| = constant implies that 1. r (t) either doesn't change with t, r '(t)=0 or 2. its...would change also by the triangle inequality. In either case since 1. r '(t)=0 or 2. r (t) dot r '(t) = r (t) r '(t)cos(90) = 0...
1 Answers · Science & Mathematics · 17/04/2015
r ^2+3r-2 = 0 Factorize the equation. then ( r +1)( r -3) = 0 Therefore, r = -1 & 3
3 Answers · Science & Mathematics · 14/10/2008
R ' or also known as R -prime can, but doesn't always have to be the original R . It's there to show you that you can place any other alkane substitute in that...
3 Answers · Science & Mathematics · 24/04/2010
0.2 + r = 0.2r − 0.06 + 0.3r Fist, let's simplify the right side side: r + 0.2 = 0.5r − 0.06 Next, isolate r and simplify. ( r + 0.2) - 0.5r - 0.2...
12 Answers · Science & Mathematics · 16/10/2007
... consists of: r = radius measure(magnitude) theta = angle measure(... ( a , ib) is now ( r *cos(theta) , r *sin(theta) Finally: your answer...
2 Answers · Science & Mathematics · 31/05/2008
description of r : look at the figure where potential is required at point P ...)----------------------. (P) .... <----------- r ---------> r & Q are given k = 8.987 X 10^9 N...
3 Answers · Science & Mathematics · 01/02/2011
I = (2V/ R ) + 2r I - (2V/ R ) = 2r r = (1/2) * [I - (2V/ R ... - IR r = (2V - IR) / 2I r = (V/I) - ( R /2)
3 Answers · Science & Mathematics · 16/01/2014
C=K(Rr/ R - r ) Divide both sides by K: C/K = (Rr... = Cr/K Extract R : R (C/K - r ) = Cr/K Divide both sides by (C/K - r ...
4 Answers · Education & Reference · 05/10/2009
If f is a *surjective* homomorphism from R to R ' then R /ker(f) and R '...ker(f) to f(x) is an isomorphism--- so, in particular, R /ker(f) is isomorphic to f( R ). But...
1 Answers · Science & Mathematics · 24/07/2011
r -(13/3)=(3/2) r =(3/2)+(13/3) r =(9/6)+(26/6) r =35/6 r =5.8333 or 5 and 5/6
3 Answers · Science & Mathematics · 06/11/2009